Exploring virtual reality painting technology and its potential for artistic purposes - Lam, Choon Khee (Nanyang Technological University, 2023)
With new and emerging technologies, art is becoming more fluid and taking on a myriad of novel and innovative forms. Multidimensional technologies such as virtual reality (VR) have opened up new opportunities and facilitated complex and inventive ways of creating, illustrating, and immersively experiencing art.